Key considerations in planning and designing programmatic assessment in competency-based medical education. (3rd July 2021) - Ross, Shelley; Hauer, Karen E.; Wycliffe-Jones, Keith; Hall, Andrew K.; Molgaard, Laura; Richardson, Denyse; Oswald, Anna; Bhanji, Farhan; ,
Abstract: Programmatic assessment as a concept is still novel for many in clinical education, and there may be a disconnect between the academics who publish about programmatic assessment and the front-line clinical educators who must put theory into practice. In this paper, we clearly define programmatic assessment and present high-level guidelines about its implementation in competency-based medical education (CBME) programs. The guidelines are informed by literature and by lessons learned from established programmatic assessment approaches. We articulate five steps to consider when implementing programmatic assessment in CBME contexts: articulate the purpose of the program of assessment, determine what must be assessed, choose tools fit for purpose, consider the stakes of assessments, and define processes for interpreting assessment data. In the process, we seek to offer a helpful guide or template for front-line clinical educators. We dispel some myths about programmatic assessment to help training programs as they look to design–or redesign–programs of assessment. In particular, we highlight the notion that programmatic assessment is not 'one size fits all'; rather, it is a system of assessment that results when shared common principles are considered and applied by individual programs as they plan and design their own bespoke model of programmatic assessment for CBME in their unique context.